Improvement of 3D Printing Elongation Using a Continuous Vibrator Device - Techawinyutham, Laongdaw; Sangkharat, Thanapat (Applied Science and Engineering Progress, 2025)
3D printing is increasingly used in various industries due to its ability to easily fabricate complex shape parts. However, the low mechanical properties of 3D-printed parts remain a major drawback. Numerous studies have focused on enhancing mechanical properties through material improvements, process optimization, and high-strength reinforcement materials. However, limited research has explored the effect of continuous vibration on interlayer bonding and mechanical properties, an area that remains largely unstudied. A vibration device was attached to the printer base, generating vibration during the printing process. Dog-bone-shaped workpieces were printed in horizontal (x-y plane) and vertical (z-axis) orientations using three vibration frequencies: 50 Hz, 77 Hz, and 105 Hz, with a fixed amplitude of 0.03 mm. The results revealed that vibration improved interlayer bonding and the elongation of samples but had no significant effect on tensile strength, while surface roughness was slightly poorer compared to non-vibrated samples. At 50 Hz, elongation increased by 62.7% for horizontal workpieces and 21.6% for vertical ones. Similarly, at 77 Hz and 105 Hz, elongation improvements were 95.2% and 98.1% for horizontal workpieces, and 20.1% and 22.8% for vertical ones, respectively. Optical microscopy analysis showed that the enhanced elongation was due to increased interlayer adhesion, as the vibration facilitated material insertion between layers.